Acts and procedures concerning procedure-related deaths in South Africa - Stefan Jansen van Vuuren (AOSIS, 2013)
Background: The act regarding procedure-related deaths in South Africa has changed recently (in 2007) and comprises a more encompassing description of possible procedure-related deaths. It subsequently includes unnatural deaths in cases where the patient died during aprocedure, or as a result of a procedure, or where it can be shown that any aspect of such a procedure has been a contributory cause. The act does not qualify the 'procedure' and by definition includes all procedures, including anaesthesia. Objective: The objective of this article is to bring awareness to general practitioners regarding the legal requirements when dealing with suspected procedure-related deaths, and to outline some of the regulations pertaining to the management of such incidents. Methods: A thorough study, interpretation and clarification of the new legislature on procedure-related deaths were performed. Discussion: The onus of deciding which procedure-related deaths are unnatural has been removed from the doctor as the new act includes all such deaths. Certain aspects of the acts remain difficult to interpret and consultation with the appointed forensic pathologist in your area is still essential in all cases of a suspected procedure-related death. Healthcare workers should acquaint themselves with all these regulations and acts that are readily available in the Government Gazette.